Collaborative clusters: A customer focused innovative approach for product development - (:unkn) unknown (INT ASSOC ENGINEERS-IAENG, 2008)
Recent developments in the competitive global environment have been forcing the Original Equipment Manufacturers (OEMs) and the supplier segment in the NI-Cycle of product development to find creative solutions of cooperation by eliminating time- and resource-waste, of competition against each other. These work mainframes the way to integrated product development by building up collaborative clusters (CC). http://www.iaeng.org/publication/WCE2008/WCE2008_pp1278-1283.pdf
Keywords: cluster; collaboration; concurrent engineering; integrated product development; DESIGN